Exploring the noncovalent interaction between β-lactoglobulin and flavonoids under nonthermal process: Characterization, physicochemical properties, and potential for lycopene delivering - Gongshuai Song; Fang Li; Ziming Xu; Nengliang Jiang; Danli Wang; Tinglan Yuan; Ling Li; Jinyan Gong (Food Chemistry: X)
The poor structure stability and low bioavailability of lycopene (LY) hampers the wide application in food field. Thus, it is crucial to explore novel deliver carrier for LY based on protein-flavonoid complexes. In this study, the noncovalent interaction mechanism between β-lactoglobulin (β-LG) and flavonoids (apigenin (API), luteolin (LUT), myricetin (MY), apigenin-7-O-glucoside, luteolin-7-O-glucoside, and myricetrin) under ultrasound treatment was explored. Results revealed that ultrasound treatment promoted reactive groups exposure and structural unfolding of β-LG to interact with six flavonoids. The main driving force between β-LG and flavonoids was hydrophobic interaction. The docking result showed that the preferred binding site for these flavonoids was on the outer surface of β-LG. The thermal stability, surface hydrophilicity, and antioxidant properties of β-LG-API, β-LG-LUT, and β-LG-MY complexes were superior by multi-spectroscopy methods and molecular simulation analysis (P < 0.05). The ability of β-LG-API for delivering LY was the best among above three binary complexes, revealing superior environmental stability and bioavailability of the β-LG-API-LY complex. This study will help to understand the ultrasound-assisted noncovalent binding of protein-flavonoid complexes, and exhibit the potential as a novel delivery system for delivery and protection of LY.